Enhanced osteogenic potential of spider silk fibroin-based composite scaffolds incorporating carboxymethyl cellulose for bone tissue engineering - Woong Jin Lee; Kyoungjoo Cho; Dayoon Lee; Seungmin Lee; Hyojae Jeon; Aaron Youngjae Kim; Gyung Whan Kim (Biomaterials and Biosystems)
This study aimed to investigate the characteristics of composite scaffolds that combine fibroin derived from spider silk and carboxymethyl cellulose (CMC) in the field of bone tissue engineering. Fibroin, obtained from spider silk, serves as a valuable biomaterial and constitutes the primary component of fibrous protein-based spider silk threads. To enhance the binding efficiency in bone formation after scaffold implantation, CMC was integrated into fibroin, aiming to improve the injectability properties of the scaffold in bone substitutes. For bone marrow mesenchymal stem cell (BMSC) tissue engineering, BMSCs isolated from mice were seeded onto the scaffold, and the rate of cell proliferation was assessed. The composite scaffold, with the addition of CMC to fibroin, exhibited superior characteristics compared to scaffolds containing only silks, including porous morphology, porosity, surface wettability, water absorption, and thermal properties. Alkaline phosphatase activity in BMSCs was significantly higher in the CMC-containing scaffold compared to the silk-only scaffold, and the CMC-containing scaffold demonstrated increased expression of osteocyte marker genes and proteins. In conclusion, the biocompatibility and hydrophilicity of CMC-containing scaffolds play essential roles in the growth and proliferation of osteocytes. Furthermore, the CMC-containing scaffold design proposed in this study is expected to have a substantial impact on promoting ossification of BMSCs.